Introducing Microsoft Teams Understanding the New Chat-Based Workspace in Office 365 - Ilag, Balu N. (Apress, 2018)
Gain industry best practices from planning to implementing Microsoft Teams and learn how to enable, configure, and integrate user provisioning, management, and monitoring. This book also covers troubleshooting Teams with step-by-step instructions and examples. Introducing Microsoft Teams gives you the comprehensive coverage you need to creatively utilize Microsoft Teams services. The author starts by giving an introduction to Microsoft Teams and its architecture followed by optimizing the Teams experience where he describes how organizations can prepare for Teams and enhance existing services. He further shows you how to manage and control the Microsoft Teams experience along with its capabilities and enhancements. You'll learn how to migrate from Skype for Business to Microsoft Teams with a step-by-step tutorial. Finally, you'll get to grips with Teams troubleshooting and best practices. This book has detailed coverage that helps you exploit every capability Microsoft Teams has to offer. It provides the answers you need and the insight that will make your journey from Skype for Business to Teams easier. You will: Enable guest access in Teams Provision and manage users in Teams Administrate Teams and channels Optimize the Teams experience Enable and configure Microsoft Teams Prepare your network for Microsoft Teams and Office 365 services Migrate from Skype for Business to Microsoft Teams.